Experimental evaluation of green nanofluids in heat exchanger made oF PDMS - Nobrega, Glauco; Souza, Reinaldo; Cardoso, Beatriz; Afonso, Inês; Pereira, José; Cardoso, Elaine [UNESP]; Moita, Ana; Ribeiro, João; Lima, Rui (Elsevier, 2024)
Conventional methods for synthesizing metallic nanoparticles face challenges such as instability and environmental concerns. Therefore, new, simpler, and more eco-friendly methods are being explored. In this context, the study reports a green synthesis process to produce magnetic iron oxide nanoparticles using an aqueous extract of the alga Chlorella vulgaris. This process leverages natural resources to create a sustainable nanofluid known as green nanofluid. To evaluate the characteristics of this nanofluid, experimental measurements of wettability, viscosity, thermal conductivity, and qualitative stability analysis were conducted. An experimental setup consisting of a heat exchanger made of polydimethylsiloxane (PDMS) was used to assess the thermal performance and the results were compared to theoretical equations and numerical simulation. Additionally, thermographic imaging of temperature gradients as the fluids passed over the heated surface of the serpentine channel were made. The main findings confirmed that the nanofluid was more stable than that obtained by traditional methods and had a more uniform temperature distribution over the heat exchanger. The higher concentration exhibited superior thermal performance compared to DI-Water. Moreover, the green nanofluid was used at a weight concentration of 0.1 wt%, provided thermal performance results of nearly 4.5% superior to those estimated by the numerical model and 6.4% higher than those experimentally obtained with the base fluid, respectively. Finally, the results obtained for the nanofluid also showed an average increase of around 5% in the viscosity of the base fluid, with a more significant sedimentation at a concentration of 0.1 wt%.
Keywords: Green nanofluids; PDMS exchanger; Stability; Thermal conductivity